Instituição de Longa Permanência para Idosos e seus processos educativos - Costa, Reijane Salazar (2015)
This study’s directive was to describe and comprehend educational processes developed in the relations between elderly residents in a Long-stay Institution for the Elderly (LSIE) as well as the elderly and people who attend and/or work in this facility. The field work was carried at the Elder Shelter "Dona Helena Dornfeld" in the city of São Carlos/SP throughout March and August 2014. Its development was held theoretically and methodologically by the Popular Education orientation, characterizing itself as a qualitative research with guiding principle the dialogue and the coexistence in which the researcher entered into the field performing participant observations, recording on field diaries as well as interview with and elderly woman who resided at the shelter. The data was analyzed from Minayo’s (2007) thematic approach, enabling the understanding of the relations set afterwards by a word, phrase or a summary that allowed a bundle of relations. From the data analysis three categories emerged, which were: I – "Being old", where the elderly woman under interview talked about positive and negative aspects of being old; II–“Living-Residing”, in which educational processes were unveiled regarding to having concrete experiences when being with other people who were previously not familiar to the elderly meaningful experiences towards life, coexistence, the creation of strategies for well-living in a new space, the realization of new realities and the crafting of a new set of skills and, finally, the third category: III– "Defiance-Compliance", from which educational processes emerged linked to the change of posture along many life situations, such as defiance, compliance and acceptance by the elderly new reality (residents at a shelter). This research brings forth contributions to the Education field by opening new paths to think and rethink human development by aiding in the exercise of reproducing a vision of our world. It also conveys contributions by highlighting educational processes at a LSIE and, in this way, carrying on the act of teaching-learning-teaching as present in the social practices outside the school. It also underwrites policies for elderly care by outlining reflections and actions at assistive spaces for the elderly person, in order to ensure that human rights are respected and well met, so that planning and functioning of these spaces are organized in a way to ensure the participatory management and the involvement of all parts interested.